Paraganglioma of the urinary bladder initially diagnosed as gastrointestinal stromal tumor requiring combined resection of the rectum: a case report - Natsumi Matsuzawa; Takeshi Nishikawa; Riki Ohno; Masaharu Inoue; Yu Nishimura; Tomomi Okamoto; Takao Shimizu; Takahide Shinagawa; Yusuke Nishizawa; Shinsuke Kazama (World Journal of Surgical Oncology, 2022)
Abstract Background Paraganglioma of the urinary bladder (Pub) is rare and presents with clinical symptoms caused by catecholamine production and release. The typical symptoms of Pub are hypertension, macroscopic hematuria, and a hypertensive crisis during micturition. The average size of detected Pubs is approximately 3 cm. Herein, we report a case of a large Pub in which the symptoms were masked by oral medication, precise preoperative diagnosis was difficult, and intraoperative confirmation of tumoral adhesion to the rectum resulted in hypertensive attacks during surgery. Case presentation A 64-year-old Japanese male with a history of hypertension and arrhythmia controlled with oral medication presented with a large tumor in the pelvic region, detected on examination for weight loss, with no clinical symptoms. Computed tomography and magnetic resonance imaging revealed a tumor measuring 77 mm in diameter in the posterior wall of the urinary bladder. The border with the rectum was unclear, and the tumor showed heterogeneous enhancement in the solid part with an enhancing hypodense lesion. Cystoscopy revealed compression of the bladder trigone by external masses; however, no tumor was visible in the lumen. Endoscopic ultrasonography-guided fine-needle aspiration revealed CD34-positive spindle-shaped cells in the fibrous tissue, suggestive of a mesenchymal neoplasm. The tumor was suspected to be a gastrointestinal stromal tumor, and surgery was performed. After laparotomy, we suspected that the tumor had invaded the rectum, and total cystectomy and anterior resection of the rectum were performed. Histologically, the tumor cells had granular or clear amphophilic cytoplasm with an oval nucleus and nests of cells delimited by connective tissue and vascular septations. Immunohistochemically, the tumor was positive for chromogranin A, CD56, and synaptophysin, and a diagnosis of paraganglioma of the urinary bladder was confirmed. There was no tumor recurrence at the 7-month follow-up. Conclusion This case highlights the importance of careful examination of pelvic tumors, including endocrine testing, for detecting paraganglioma of the urinary bladder in patients with a history of hypertension or arrhythmia.